Analisis Yuridis Tindak Pidana Kekerasan Dalam Rumah Tangga Dalam Perkawinan Dibawah Tangan Ditinjau Dari Undang-Undang Nomor 23 Tahun 2004 tentang Penghapusan Kekerasan Dalam Rumah Tangga - Aulia, Dita; Faisal, Faisal; Toni, Toni (JURNAL PENELITIAN SERAMBI HUKUM, 2025)
Domestic violence in an under-aged marriage is a criminal offense that is not clearly regulated in positive law, resulting in unfulfilled legal protection for the community. The purpose of this study is to determine and analyze how the criminal conviction of perpetrators of domestic violence in an underhanded marriage is reviewed from Law Number23 of 2004 concerning the Elimination of Domestic Violence and to determine and analyze the legal interpretation in the criminal conviction of perpetrators of domestic violence in an underhanded marriage in terms of Law Number 23 of 2004 concerning the Elimination of Domestic Violence. The type of research used is normative research, with a conceptual approach and statutory approach to data collection techniques through literature study with qualitative analysis techniques. The results of this study indicate that criminal convictions in cases of domestic violence in underhanded marriages can be charged using Law Number 23 of 2004 concerning the Elimination of Domestic Violence due to the systematic interpretation of Law Number 1 of 1974 concerning Marriage that underhanded marriage is a legal marriage. So that domestic violence in an under-aged marriage can be charged using Law Number 23/2004 on the Elimination of Domestic Violence.